The effects of pest-resistant amaranth accessions on the performance of the solitary Endoparasitoid apanteles hemara (Hymenoptera: braconidae) against the amaranth leaf-webber Spoladea recurvalis (Lepidoptera: crambidae) - Othim, S.T.O.; Ramasamy, S.; Kahuthia-Gathu, R.; Dubois, T.; Ekesi, S.; Fiaboe, K.K.M. (Oxford University Press, 2019)
The leaf-webber Spoladea recurvalis F. is the most devastating pest of amaranths in East Africa. Recent collaborative research in Asia and East Africa revealed one highly resistant amaranth accession (VI036227) to the pest and seven moderately resistant ones (RVI00053, VI033479, VI044437-A, VI047555-B, VI048076, VI049698, and VI056563). The solitary koinobiontic endoparasitoid Apanteles hemara Nixon has also been reported as efficient against the pest. Plant resistance to herbivores may have bottom-up effects on their parasitoids. In this study, we assessed the effects of the seven moderately resistant amaranth accessions and one susceptible accession (VI033482) on the performance of A. hemara. Except VI056563 that recorded lower parasitism rates compared to the susceptible accession, A. hemara performed well on all the other moderately resistant accessions. The longevity of the parasitoid was significantly extended on the resistant accessions compared to the susceptible one. While the parasitoid’s body size, developmental time, and survival differed significantly between resistant accessions, they were similar to results obtained on the susceptible accession. Furthermore, while the parasitoid’s sex ratio was male-biased in the susceptible accession, balanced sex ratios were obtained from accessions RVI00053, VI033479, VI044437-A, VI047555-B, VI048076, and VI049698. Significant nonreproductive host larval mortality was induced by A. hemara on all the tested accessions. These results suggest that the moderately resistant accessions can be used in combination with the endoparasitoid A. hemara to manage S. recurvalis and other amaranth leaf-webbers in the context of integrated pest management.